2021
DOI: 10.1039/d1ra04461c
|View full text |Cite
|
Sign up to set email alerts
|

Newly synthesised oxime and lactone derivatives from Dipterocarpus alatus dipterocarpol as anti-diabetic inhibitors: experimental bioassay-based evidence and theoretical computation-based prediction

Abstract: Dipterocarpus alatus-derived products are expected to exhibit anti-diabetes properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…According to the theoretical interpretation as given, the most effective ligand-3W37 inhibitory structures are 8-3W37 (DS −12.9 kcal·mol −1 ; RMSD 1.29 Å) > 4-3W37 (DS −12.3 kcal·mol −1 ; RMSD 1.37 Å); the significance is defined as DS < −12 kcal·mol −1 , which is thought to correspond with the ability to induce effective inhibitory effects. In fact, our preceding works correlated this range with assay-based IC 50 values < 50 μM (control drug IC 50 ca 300 μM), 35,36 which were considered effective inhibition against the enzymatic activity of α-glucosidase. In terms of ligand-PTP1B inhibitory structures, the corresponding order is 8-PTP1B (DS −13.4 kcal·mol −1 ; RMSD 1.75 Å) > 4-PTP1B (DS −13.1 kcal·mol −1 ; RMSD 1.49 Å) > 2-PTP1B (DS −12.9 kcal·mol −1 ; RMSD 1.17 Å); the significance is defined by comparison to the D-PTP1B complex (ie DS −12.8 kcal·mol −1 ; RMSD 1.50 Å).…”
Section: Resultsmentioning
confidence: 94%
“…According to the theoretical interpretation as given, the most effective ligand-3W37 inhibitory structures are 8-3W37 (DS −12.9 kcal·mol −1 ; RMSD 1.29 Å) > 4-3W37 (DS −12.3 kcal·mol −1 ; RMSD 1.37 Å); the significance is defined as DS < −12 kcal·mol −1 , which is thought to correspond with the ability to induce effective inhibitory effects. In fact, our preceding works correlated this range with assay-based IC 50 values < 50 μM (control drug IC 50 ca 300 μM), 35,36 which were considered effective inhibition against the enzymatic activity of α-glucosidase. In terms of ligand-PTP1B inhibitory structures, the corresponding order is 8-PTP1B (DS −13.4 kcal·mol −1 ; RMSD 1.75 Å) > 4-PTP1B (DS −13.1 kcal·mol −1 ; RMSD 1.49 Å) > 2-PTP1B (DS −12.9 kcal·mol −1 ; RMSD 1.17 Å); the significance is defined by comparison to the D-PTP1B complex (ie DS −12.8 kcal·mol −1 ; RMSD 1.50 Å).…”
Section: Resultsmentioning
confidence: 94%
“…In the previous investigation [ 53 ], theoretical complexes of the tetrylone family with E HOMO values of − 3 to − 7 eV were also found as highly stable. It has been evidenced that all structures possess an insulation-to-semiconduction energy gap (3.2 eV < EG < 9 eV), showing good intermolecular binding capability toward protein structures [ 54 ], and this was further explained based on the super-exchange theory [ 55 , 56 ] and the electron hopping model [ 57 ]. In this study, the energy gap values of the inhibitors were found in the range of 3.77 to 5.61 eV; as such, they have potential intermolecular binding capability toward the targeting enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…If subjected to a nonequivalent reference to our experiment-correlated works on single-enzymatic inhibition, these values might be referred to as effective inhibitors against α-glucosidase (assaying-based IC50 values < 100 μM). 37,38 Therefore, the G. lucidum extracts, in general, and 1 (Butyl lucidenate P), 2 (Butyl lucidenate E2), 11 (Methyl ganoderate H), 13 (Methyl lucidenate N), in particular, are highly recommended for further experimental validation from enzymatic bioassays.…”
Section: Resultsmentioning
confidence: 99%